EFFECTS OF CHITOSAN COATING ON THE PHYSICAL, MECHANICAL AND ANTIMICROBIAL PROPERTIES OF FOOD PACKAGING PAPER - Kurnia Wiji Prasetiyo; Deni Zulfiana; Sita Heris Anita; Widya Fatriasari; Lisman Suryanegara; Nanang Masruchin; Sesmi Gutari (Jurnal Sains Materi Indonesia, 2020)
EFFECTS OF CHITOSAN COATING ON THE PHYSICAL, MECHANICAL AND ANTIMICROBIAL PROPERTIES OF FOOD PACKAGING PAPER. The coating process on food packaging paper is carried out to improve the food safety and health aspect from dangerous substance migration from food packaging into food. Chitosan has attracted interest in packaging, especially in food packaging as edible films and coatings. A paper from oil palm empty fruit bunches (OPEFB) pulp was coated with chitosan using different pulp weight (1, 1.5, 2 g) and chitosan content (0.25, 0.50, 0.75, 1 g) as parameters. The effect of chitosan as coating material on physical, mechanical, and antimicrobial properties was studied. The results showed that the density and grammage values of the paper increased after coating due to the increasing of chitosan content. The mechanical properties of the coated paper, such as tensile strength, tensile modulus and elongation, improved in line with the increase of chitosan content and pulp weight. The addition of chitosan on paper imparts antimicrobial properties against Gram-positive bacteria (Staphylococcus aureus) and Gram- negative bacteria (Escherichia coli).